Fragmenta Hesiodea - Hesiodus (e typographeo Clarendoniano, 1999)
This is a complete critical edition of the extant remains of the lost narrative and didactic poems anciently ascribed to Hesiod. The book incorporates material from the latest papyri published before 1967, particularly in relation to the Catalogue of Women. For all eleven works, which include the Melampodia, The Marriage of Ceyx, The Great Works, the Idaean Dactyles, and the Astronomy, the editors give improved texts and new interpretations of many fragments included in earlier editions. All the papyrus fragments old and new have been carefully collated, and full advantage has been taken of modern editions of those authors who preserve fragments in quotation. In addition to the usual critical apparatus, there are brief notes on the subject matter, sections of uncertain and spurious attributions, and full indices. (S ovitka)